Meaning of Creative Campaign in Arief Muhammad’s Billboards ‘Ready to be Number 1’ (Roland Barthes Semiotics Analysis) - Stevani; Patricia Robin (Jurnal Multidisiplin Madani, 2023)
Billboards are one of the outdoor promotional media used to convey information or notifications to the public, which are usually used by many legislative candidates to carry out political campaigns. One of the viral billboards that was in the spotlight in 2020 because it looked like it was carrying out a political campaign, was when Arief Muhammad's face was surprisingly complete with the words 'Ready to Be Number 1' emblazoned on a street corner located in Bintaro, South Jakarta, which was interpreted by the public will plunge into the world of politics in Indonesia. The purpose of this study is to focus on how a billboard can support marketing performance through a creative campaign that is packaged with a guerilla marketing strategy using Roland Barthes' semiotics, to produce denotative, connotative, mythical meanings, along with the findings of the ideology of capitalism and nationalism on these viral billboards. The results of this study indicate that all verbal and nonverbal signs on the billboard 'Ready to Be Number 1' are interpreted as a form of Arief Muhammad's seriousness in acquiring, promoting, and making Prepp Studio the number 1 men's fashion brand in Indonesia, under his leadership with Dimas Mairyan’s. The researcher concludes that the 'Ready to Be Number 1' billboard tries to take advantage of the momentum of the 2020 Regional Head Election campaign to support the campaign so that it becomes stronger with political overtones